NOTARY ROLE IN THE IMPLEMENTATION OF EXECUTION PROCUREMENT OF GOODS AND SERVICES ARE FREE OF CORRUPTION BASED ON THE PRINCIPLE OF GOOD GOVERNANCE - Aris Yulia (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Indonesian is one country in the world that are struggling and crave the creation of good governance. However, the current situation shows that it is still very far from expectations. Political interests, corruption, unfair judicial, work outside the authority, and the lack of integrity and transparency are some of the issues that make a good government still can’t be reached. To achieve good governance in governance in Indonesia, the principles of good governance should be enforced in a variety of key government institutions. Rules and regulations covering government procurement of goods and services are relatively very dynamic and responsive to the growing variety of circumstances. One form of action that may result in unfair competition is a conspiracy in the tender, which is one of the activities prohibited by Law No. 5 Year 1999. The tender conspiracy (or collusive tendering) occurs when businesses, which should compete closed, conspired to raise prices or lower the quality of the goods or services for buyers who wish to acquire products or services through a procurement process. Notary deed as the participants in the tender can also be used as a subject in the tender conspiracy. With implement the principles of good governance, the three pillars, namely governments, corporations, and civil society should look after each other, support each other and actively participate in governance is being done Keywords: Notary, Non Corruption, Good Governance.